1992
DOI: 10.1007/bf00987827
|View full text |Cite
|
Sign up to set email alerts
|

6,10,14-Trimethylpentadecan-2-one: A Bermuda grass phagostimulant to fall armyworm (lepidoptera: Noctuidae)

Abstract: A phagostimulant, 6,10,14-trimethylpentadecan-1-one (phytone), was isolated and identified from Bermuda grass,Cynodon dactylon (L.). The phagostimulant activity of this isoprenoid ketone was established from bioassays of fall armyworm larvae,Spodoptera frugiperda (J.E. Smith). Larvae displayed increased body mass accumulation as well as preference to diet supplemented with this molecule. Neonate larvae fed diet supplemented with chromatographic isolates of phytone-containing fractions from six Bermuda grass cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In addition, it serves as a phagostimulant of Bermuda grass to larvae of the fall armyworm, Spodoptera litoralis. [42] The respective alcohol 21 is a male pheromone of the butterfly Bicyclus anynana, [43] while (E)-phytol (23) serves this function in males of the moth Ephestia elutella. It evokes female-courtship response in mixtures with 4-decanolide or 4-undecanolide.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it serves as a phagostimulant of Bermuda grass to larvae of the fall armyworm, Spodoptera litoralis. [42] The respective alcohol 21 is a male pheromone of the butterfly Bicyclus anynana, [43] while (E)-phytol (23) serves this function in males of the moth Ephestia elutella. It evokes female-courtship response in mixtures with 4-decanolide or 4-undecanolide.…”
Section: Discussionmentioning
confidence: 99%
“…A diterpenoid, phytol was of the highest concentration (21.00%) in the extract (Fig.1). Phytol-rich extract have been reported to exhibit antimicrobial (Fitsiou et al, 2007;Radulovic et al, 2011) alleopathic (Razavi and Nejad-Ebrahimi, 2010) and insecticidal activities (Mohamed et al, 1992). From the spectrophotometric analysis, flavonoids and saponins were estimated as 6.25 mg rutin/g and 5.18 mg ginsenoside/g respectively (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…This somaclone maintained the same yield, persistence, and forage nutritional quality parameters as the parent. Biochemieal tests showed that the somaclone had lower levels of an insect feeding stimulant (Mohamed et al, 1992). This somaclone maintained the positive agronomie traits of the parent cultivar, but had a change in the production of a secondary metabolite that conferred increased resistance to fall armyworm.…”
Section: Somaclonal Variation In Forage Grassesmentioning
confidence: 95%